2016
DOI: 10.1590/2179-8087.030513
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do Tipo de Chapa de Partículas nas Propriedades Físicas e Mecânicas

Abstract: RESUMOEste trabalho teve como objetivo avaliar chapas de partículas do tipo aglomerado convencional, chapas tipo Medium Density Particleboard (MDP) e as do tipo aglomerado com inclusão laminar. As chapas avaliadas foram fabricadas com partículas de Acacia mangium e no aglomerado com inclusão laminar utilizaram-se lâminas de Schizolobium amazonicum. O aglomerado convencional e o aglomerado com inclusão laminar apresentaram umidade de equilíbrio higroscópico estatisticamente superior ao MDP. O aglomerado com inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Figure 4(a, b) showed that, in numerical values, there is an increasing trend in strengths according to the bamboo percentage increase, although the results have demonstrated a statistical equivalence. Cabral et al (2016) found the mean value of 14.89 MPa for the static bending in modulus of rupture of medium-density particleboards based on Acacia mangium wood. Melo et al (2015) verified the static bending for different wood and bamboo proportions (0%, 25%, 50%, 75%, and 100%) of lignocellulosic particleboards based on ureaformaldehyde resin.…”
Section: Resultsmentioning
confidence: 96%
“…Figure 4(a, b) showed that, in numerical values, there is an increasing trend in strengths according to the bamboo percentage increase, although the results have demonstrated a statistical equivalence. Cabral et al (2016) found the mean value of 14.89 MPa for the static bending in modulus of rupture of medium-density particleboards based on Acacia mangium wood. Melo et al (2015) verified the static bending for different wood and bamboo proportions (0%, 25%, 50%, 75%, and 100%) of lignocellulosic particleboards based on ureaformaldehyde resin.…”
Section: Resultsmentioning
confidence: 96%
“…Following the trend of sustainable development combined with the objectives set by Agenda 2030 (UN, 2015), which values inclusive industrialization and sustainable production and consumption patterns, it is understood that the use of this by-product of jupati for the production of particleboards can be a viable alternative to give them a better use and at the same time, create an innovative material. It is noteworthy that, including new raw materials in products such as panels, becomes a major attraction in the area of industrialization, solving, in part, the environmental problem caused by waste, in addition to meeting the demand for raw materials, also causing a reduction in its costs, adding value to the final product (Cabral et al, 2016).…”
Section: Introductionmentioning
confidence: 99%